Manajemen Pembinaan Mental Anak Berkebutuhan Khusus di Sekolah Menengah Pertama Negeri Kota Banjarmasin - Rahmiyati Rahmiyati; Hapiz Al Ansyari (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
Children with special needs also have the right to develop mental and spiritual aspects so that they develop optimally according to their circumstances. In part, education has been equalized by all in the city of Banjarmasin, but there are still obstacles that require careful planning management. For this reason, research was conducted with the aim of uncovering and describing plans for mental development of children with special needs in junior high schools. This research method is descriptive qualitative, using interview, observation and documentary data collection instruments. Data processing and analysis with data collection, data display, data redction, conclusion: drawing/verification. The research findings on planning management for mental development of children with special needs are (1) analysis of student needs, (2) recruitment of students, (3) selection of students, (4) orientation of students, (5) placement of students, and (6) student recording and reporting